FORMULASI CANGKANG KAPSUL DARI PEKTIN KULIT BUAH NANGKA (Artocarpus heterophyllus Lam) DAN UJI WAKTU HANCUR KAPSUL - Rosiana Rizal; Salman Salman; Eka Wulandari (Universitas Islam Bandung, 2023)
Capsule is capsule preparations which consisting of a drug in a soft capsule and hard capsule sell. Capsule is the preparations that most people used to discover the unpleasant taste of the drug. Most of capsule sell are made of gelatin, but it can also made with starch or other ingredients. The other ingredientsÂ which can substitute gelatin is pectin. Pectin is an ingredient belong to the class of carbohydrates. This study aim to find others alternative that can be used as new ingredients of capsule sell, which is jack fruit peels. Dissolved 20 mg jack fruit peels in 1000 ml of distilled water and, added 5% of citric acid. Then extracted on a hot plate with a stirring speed 600 rpm, temperature of 85Í¦C, for 120 minutes. The yield obtained was 0.319%. The best formulations results were 2 (0.7 gram pectin, 5.00 gram carrageenan, 100ml disttiled water). The result of the evaluation of capsule sell standards with a body diameter of 6,2 mm, 6,3 mm, of a lid diameter, a body length of 15,2 mm, a lid length of 07.8 mm, and those that are unqualified with 0.09 gram of capsule weights. The organleptic results are light brown color, texture a little loud and there is no fragrance. The capsule sell disintegration should meet the requirements set by the Indonesian Pharmacopoeia V edition, is 13 minutes 47 seconds.Keywords: jackfruit skin (Artocarpus heterophyllus Lam), pectin, capsule shell